Prevalence of cryptococcal antigen (CrAg) among HIV-positive patients in Eswatini, 2014-2015 - Samson M. Haumba; Mitsuru Toda; Rossana Jeffries; Peter Ehrenkranz; Munyaradzi Pasipamire; Trong Ao; Nomthandazo Lukhele; Sikhathele Mazibuko; Mandzisi Mkhontfo; Rachel M. Smith; Tom Chiller (AOSIS, 2020)
Background: Cryptococcal meningitis is a leading cause of death amongst people living with HIV. However, routine cryptococcal antigen (CrAg) screening was not in the national guidelines in Eswatini. Objectives: A cross-sectional study was conducted between August 2014 and March 2015 to examine CrAg prevalence at Mbabane Government Hospital in Eswatini. Methods: We collected urine and whole blood from antiretroviral-therapy-naïve patients with HIV and a cluster of differentiation 4 (CD4) counts 200 cells/mm3 for plasma and urine CrAg lateral flow assay (LFA) screening at the national HIV reference laboratory. Two CD4 cut-off points were used to estimate CrAg prevalence: CD4 100 and 200 cells/mm3. Sensitivity and specificity of urine CrAg LFA was compared to plasma CrAg LFA. Results: Plasma CrAg prevalence was 4% (8/182, 95% confidence interval [CI]: 2-8) amongst patients with CD4 counts of 200 cells/mm3, and 8% (8/102, 95% CI: 3-15) amongst patients with CD4 counts of 100 cells/mm3. Urine CrAg LFA had a sensitivity of 100% (95% CI: 59-100) and a specificity of 80% (95% CI: 72-86) compared with plasma CrAg LFA tests for patients with CD4 200 cells/mm3. Forty-three per cent of 99 patients with CD4 100 were at World Health Organization clinical stages I or II. Conclusion: The prevalence of CrAg in Eswatini was higher than the current global estimate of 6% amongst HIV-positive people with CD4 100 cell/mm3, indicating the importance of initiating a national screening programme. Mechanisms for CrAg testing, training, reporting, and drug and commodity supply issues are important considerations before national implementation.